Examination of the biological effects of sunlight on the skin: a review: Sunlight effect on the skin - Razzaghi, Zahra; Ahmadzadeh, Alireza (Journal of Lasers in Medical Sciences, 2025)
Introduction: Sunlight is essential for all living beings. While certain effects of sunlight are well-established, others require further investigation. Sunlight is composed of electromagnetic spectrum radiation, which can be grouped into three main types: visible, ultraviolet (UV), and infrared (IR). UV radiation is split into three subtypes: UVA, UVB, and UVC, each of which owns unique properties and varying effects on the skin. Methods: In this review, the main databases, including PubMed, Scopus, and Google Scholar were investigated for studies examining the biological effects of sunlight on the skin by using suitable keywords and specific strategies from 2007 to 2024. All the studies that were not about sunlight and skin were excluded. Results: The influence of sunlight, particularly UV radiation can lead to a range of biological effects that may be both advantageous and detrimental. Sunlight is closely linked with common skin issues such as sunburn, skin aging, and skin cancer; therefore, the primary objective of this review is to examine the various benefits and drawbacks of sunlight exposure on human skin. The negative impact of solar radiation on the skin is especially evident with prolonged exposure, where UV radiation poses serious health risks, including squamous cell carcinoma, melanoma, and basal cell carcinoma, which are the three most common types of skin cancer. Conclusion: cancers mainly occur due to DNA damage induced by UV, especially UVB radiation. Furthermore, chronic exposure to UV radiation causes photoaging, which is characterized by the early onset of wrinkles, reduced elasticity, and alterations in skin pigmentation, all of which underscore the enduring effects of sunlight on the skin’s texture.